2022
DOI: 10.1097/rhu.0000000000001809
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Sources of Information by Patients With Rheumatic Diseases

Abstract: The aim of this study was to ascertain the frequency of use, search intent (SI), level of accessibility, and degree of reliability of sources of information (SOIs) in rheumatology. Methods:A survey among adult outpatients with rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis, and spondyloarthritis was conducted. They were asked if they had procured information from 12 selected SOIs during the past year. Search intent was defined as the source they would like to consult. Accessibility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…4 A study from Argentina reported that 36% of patients with rheumatic diseases used Facebook ® as a source of information, just behind their physician and other patients. 5 In the same vein, Callejas-Rubio JL et al reported that up to 70% of Spanish patients with systemic lupus erythematosus (SLE) used the Internet to search for information on their disease. 6 The use of SoMe by patients as health-care information sources may present both benefits and barriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A study from Argentina reported that 36% of patients with rheumatic diseases used Facebook ® as a source of information, just behind their physician and other patients. 5 In the same vein, Callejas-Rubio JL et al reported that up to 70% of Spanish patients with systemic lupus erythematosus (SLE) used the Internet to search for information on their disease. 6 The use of SoMe by patients as health-care information sources may present both benefits and barriers.…”
Section: Introductionmentioning
confidence: 99%
“…6 The use of SoMe by patients as health-care information sources may present both benefits and barriers. On the one hand, among the numerous potential benefits SoMe provides, we highlight that they (1) facilitate sharing of information and experiences, thus helping community building; (2) enable disadvantaged populations (i.e., rural, low income, and older adults) to access information and reliable health-care experts; (3) support the exchange and spread of valuable health-care information; (4) may foster patient engagement in the development of health policies; (5) may provide access to patient's opinion on the relevance of research agenda on a specific disease; and (6) offer a platform for medical education and networking for both patients and health-care providers. [7][8][9] Recent evidence supports these benefits.…”
Section: Introductionmentioning
confidence: 99%